Optimizing the gonadal performance of broodstock Helostoma temminckii with addition of enrichment ingredients in feed - INDIRA FITRILIYANI; SISWANTO SISWANTO; LUCHAS LUCHAS (Jurnal Natural, 2022)
The problem in the development of Kissing gourami fish culture was quality seeds that cannot be available continuously. Purpose of this research was to examine the need for additional enrichment materials in feed that can optimize the process of gonad maturation of Kissing gourami fish. Treatment A=Commercial feed added with Vegetable Oil, Glutathione, and Egg White; B=Commercial feed added with Vegetable Oil, Vitamin E 300 mg/Kg, Glutathione, and Egg White; C=Commercial feed added with Vegetable Oil, Vitamin E 500 mg/Kg, Glutathione, and Egg White. and D=Commercial feed added with Vegetable Oil, Vitamin E 700 mg/Kg, Glutathione, and Egg White. The results showed that all treatments with the addition of glutathione and vitamin E fortifications with levels of 300 mg-700 mg gave the effect of increasing IGS, IHS, higher fecundity and larger egg diameter than treatment A. The amount of initial IGS increase in treatment A was 33.49%, treatment B was 172.52%, treatment C was 208.60% and treatment D was 691.20%. While the IHS value at the end of the study decreased in treatment A by 35.30% and treatment C which also experienced a decrease in IHS by 26.23%. While in treatments B and D there was a not too large increase, in the range of 42.56% (B) and 5.66% (D).